space Repeats Itself”: Mapping Insecurity In Isra’s And Deya’s Spatiality In A Woman Is No Man (2019) By Etaf Rum - Bouzid Nadjet; Kerboua Salim (University of Eloued جامعة الوادي, 2025)
Home as the emblem of security and belonging is the sacred place that individuals long for and belong to. Since literature is said to be the mirror of society, projecting what happens in it and aspires to capture the essence of its people, it comes as no surprise that most literary works have home as a source of security and belonging. Nevertheless, exceptions exist. Etaf Rum’s novel A Woman is No Man (2019) depicts the story of Palestinian-American women who suffer from domestic violence and non-belonging. In the novel, Isra and her daughter Deya feel insecure in their own home because of the false cultural assumptions that prevail in some Palestinian and Arab American households. It is said that history repeats itself, but in the case of Isra and Deya space seems to repeat itself. In this regard, the present study aims at shedding light on the importance of space and how it affects the social and historical course of the characters. The study also analyses the concept of insecurity in relation to home and belonging.
Article . Ex Professo. Vol. 10. N1
Keywords: insecurity; spatiality; home; belonging; Arab-American